Synthesis and the impact of hydroxyapatite nanoparticles on the viability and activity of rhizobacteria - Bedah Rupaedah; Indrika Novella; Atiek Rostika Noviyanti; Diana Rakhmawaty Eddy; Anna Safarrida; Abdul Hapid; Zhafira Amila Haqqa; Suryana Suryana; Irwan Kurnia; Fathiyah Inayatirrahmi (Beilstein Journal of Nanotechnology)
Preserving the viability of rhizobacteria during plant application poses a significant challenge when utilizing rhizobacteria as biofertilizers, especially under adverse environmental conditions. Therefore, the selection of a suitable carrier material for rhizobacteria plays a crucial role in ensuring the sustained viability of these microorganisms. Nanomaterials, particularly nanohydroxyapatite (nHA), have garnered attention for sustaining rhizobacterial viability, high loading capacity, high biodegradability, and biocompatibility, which facilitate microbial interactions. In this study, nHA was synthesized using a hydrothermal method and used as a carrier for two rhizobacteria strains (Pd and Tb). The structural and morphological properties of nHA were examined through XRD and scanning electron microscopy analyses. Rhizobacteria were encapsulated within the carrier material, and their viability was evaluated using the total plate count method. Following their immobilization on nHA, the phosphate-solubilizing capacity of rhizobacteria was evaluated using Pikovskaya’s medium. A nitrogen-free bromothymol medium was utilized to qualitatively assess the nitrogen-fixing ability of rhizobacteria. Furthermore, rhizobacteria were identified using 16S rRNA gene sequencing, followed by analysis to construct a phylogenetic tree. nHA was found to meet the required quality criteria, exhibiting a spherical morphology with an average particle size of 68 nm and a porosity of 54.78%. The nHA carrier demonstrated favorable physical attributes to sustaining rhizobacterial viability with pH 8.95 and an electrical conductivity of 55.4 μS/cm. Rhizobacteria loaded onto the nHA carrier maintained comparable viability to those without carriers. The highest viability of the rhizobacterial strains Pd and Tb loaded onto the nHA carrier was observed on the seventh day after inoculation, measuring at 2.480 × 107 and 1.040 × 107 CFU/mL, respectively. The qualitative tests of nHA as rhizobacterial carrier demonstrated that rhizobacteria retained their ability to solubilize phosphate and fix nitrogen. Furthermore, both rhizobacteria have been identified. Pd rhizobacterium was identified with complete match to Brevundimonas olei strain Prd2. Similarly, Tb rhizobacterium showed 100% similarity to Bacillus altitudinis strain NPB34b. Based on this reseach, nanohydroxyapatite could be the potential carrier to protect rhizobacteria from external stressors and to maintain their viability over the long term. These findings indicate the potential of a nanohydroxyapatite–rhizobacteria system as a promising environmentally friendly fertilizer.